2017
DOI: 10.18632/oncotarget.14561
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30c-5p ameliorates hepatic steatosis in leptin receptor-deficient (db/db) mice via down-regulating FASN

Abstract: Approximately 15–40% of the general adult population suffers from non-alcoholic fatty liver disease (NAFLD) worldwide. However, no drug is currently licensed for its treatment. In this study, we observed a significant reduction of miR-30c-5p in the liver of leptin receptor-deficient (db/db) mice. Remarkably, recombinant adeno-associated virus (rAAV)-mediated delivery of miR-30c-5p was sufficient to attenuate triglyceride accumulation and hepatic steatosis in db/db mice. Through computational prediction, KEGG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…Similar to our findings, Das et al, have found that miR-30c-5p targeting regulates fatty acid synthase, reduces triglyceride accumulation and lipid deposition, and improves NAFLD [23]. In fact, abnormal accumulation of TG in the liver is one of the characteristics of NAFLD [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, Das et al, have found that miR-30c-5p targeting regulates fatty acid synthase, reduces triglyceride accumulation and lipid deposition, and improves NAFLD [23]. In fact, abnormal accumulation of TG in the liver is one of the characteristics of NAFLD [24,25].…”
Section: Discussionsupporting
confidence: 92%
“… 31 However, rAAV9-delivered miR-217 may also target other organs, such as the liver and kidney, and may also exert functions on these organs; thus, potential systemic effects of miR-217 should not be ruled out. 32 Organ-specific miR-217 transgenic or knockout mice can be used to regulate miR-217 expression in the heart to further explore the role of miR-217 in cardiac hypertrophy and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…rAAV9 vectors containing hsa-miR-217, hsa-miR-217-TUD, PTEN, or GFP were constructed by triple plasmid co-transfection, respectively, as described previously. 32 The vectors were purified and stored at −80°C before injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-29 and miR-486 are reported to regulate cholesterol metabolism by targeting hydroxy-3-methyl-glutaryl-CoA reductase and histone acetyltransferase-1, respectively (17,28). Furthermore, miR-30b-5p and miR-30c-5p belong to the same family of miRNAs regulating fatty acid synthesis genes, targeting elongation of very long chain fatty acids protein 5 (ELOVL5) and fatty acid synthase (FAS), respectively (18,19). miR-34a has been reported to participate in proinflammatory NAFLD (24), while miR-130a-3p directly targets transforming growth factor-β receptors 1 and 2, which may contribute to hepatic fibrosis (21).…”
Section: Discussionmentioning
confidence: 99%